A sensitive platform for DNA detection based on organic electrochemical transistor and nucleic acid self-assembly signal amplification. Issue 60 (24th November 2021) - Chen, Chaohui; Song, Qingyuan; Lu, Wangting; Zhang, Zhengtao; Yu, Yanhua; Liu, Xiaoyun; He, Rongxiang
Abstract : A new method has been developed for DNA detection by integrating hybridization chain reaction signal amplification with organic electrochemical transistor device for the first time. Abstract : Highly sensitive detection of DNA is of great importance for the detection of genetic damage and errors for the diagnosis of many diseases. Traditional highly sensitive organic electrochemical transistor (OECT)-based methods mainly rely on good conductivity materials, which may be limited by complex synthesis and modification steps. In this work, DNA biosensor based on OECT and hybridization chain reaction (HCR) signal amplification was demonstrated for the first time. Au nanoparticles were electrochemically deposited on the Au gate electrode to increase the surface area. Then, the HCR products, long negatively charged double-stranded DNA, were connected to the target by hybridization, which can increase the effective gate voltage offset of OECT. This sensor exhibited high sensitivity and even 0.1 pM target DNA could be directly detected with a significant voltage shift. In addition, it could discriminate target DNA from the mismatched DNA with good selectivity. This proposed method based on HCR in DNA detection exhibited an efficient amplification performance on OECT, which provided new opportunities for highly sensitive and selective detection of DNA.